2009
DOI: 10.1254/jphs.09094fp
|View full text |Cite
|
Sign up to set email alerts
|

The Distinct Roles of Calmodulin and Calmodulin Kinase II in the Reversal of Run-Down of L-Type Ca2+ Channels in Guinea-Pig Ventricular Myocytes

Abstract: Abstract. In this study, we investigated the roles of calmodulin kinase II (CaMKII) and calmodulin (CaM) in the reversal of run-down of L-type Ca 2+ channels. Single Ca 2+-channel activities in guinea-pig ventricular myocytes were recorded using the patch-clamp technique, and run-down of the channel activities was induced by inside-out patch formation in the basic internal solution. At 1 min after patch excision, 1 -30 μM CaMKII mutant T286D (CaMKIIT286D), a constitutively active type of CaMKII, induced the Ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
13
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 36 publications
(36 reference statements)
2
13
0
Order By: Relevance
“…Multiple factors have been identified to regulate the Cav1.2 channel through various mechanisms, including protein kinase phosphorylation and direct interaction with the channel. It is reported that the activity of the Cav1.2 channel is modulated by cAMP-dependent protein kinase (6, 16) and calmodulin (CaM) kinase II-mediated phosphorylation (14,15). Some studies indicate that CaM is directly tethered to the Cav1.2 channel and mediates the channel function (38,50,53).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Multiple factors have been identified to regulate the Cav1.2 channel through various mechanisms, including protein kinase phosphorylation and direct interaction with the channel. It is reported that the activity of the Cav1.2 channel is modulated by cAMP-dependent protein kinase (6, 16) and calmodulin (CaM) kinase II-mediated phosphorylation (14,15). Some studies indicate that CaM is directly tethered to the Cav1.2 channel and mediates the channel function (38,50,53).…”
mentioning
confidence: 99%
“…kinase II-mediated phosphorylation (14,15). Some studies indicate that CaM is directly tethered to the Cav1.2 channel and mediates the channel function (38,50,53).…”
mentioning
confidence: 99%
“…Thus we mainly focused on NP o of I Na,P , which represented channel activity. As our previous studies showed that CaM and its mutants could modulate the activity of voltage-gated Ca 2ϩ channels (13, 15), we investigated whether CaM and its mutants could modulate VGSC activity according to our previously described method for measuring NP o of the channel (14,16).…”
Section: Resultsmentioning
confidence: 99%
“…Phosphorylation of the Cav1.2 channels by CaMKII or PKA is reported to be required for channel activity [18,19]. Thus the possibility that the other nucleotides except ATP might have inhibited a protein kinase critical for maintaining channel activity cannot be excluded.…”
Section: Discussionmentioning
confidence: 99%